Context Matters: Divergent Roles of Exercise-Induced and Tumor-Derived Lactate in Cancer - Amir hossein Ahmadi Hekmatikar; Ghazal Zolfaghari; Aref Basereh; D. Maryama Awang Daud; Kayvan Khoramipour (Biomolecules, 2025)
Instead of being waste product of metabolism, lactate, has become a key metabolic and signaling molecule in both exercise physiology and tumor biology. Carcinogenic cells produce huge amounts of lactate through the Warburg effect, which is a hallmark of aggressive tumors, increasing acidity in the environment that can stimulates angiogenesis, immune evasion, and metastasis. Conversely, while exercise acutely elevates blood lactate concentration but it consider helpful for cancer patients. This paradox raises the following question: is exercise-induced lactate a friend or foe in cancer? This study reviews current evidence on the mechanistic, metabolic, immunological, and clinical impacts of exercise-induced lactate in cancer patients, highlighting the context-dependent effects that render lactate either beneficial or detrimental. Tumor-derived lactate seems to be pro-tumorigenic, driving immune suppression and disease progression, whereas short bursts of lactate from exercise can enhance anti-tumor immunity and metabolic reprogramming under the right conditions. Therefore, lactate’s impact on cancer is “all about the context”.